2000
DOI: 10.1038/sj.onc.1203496
|View full text |Cite
|
Sign up to set email alerts
|

Translation of p15.5INK4B, an N-terminally extended and fully active form of p15INK4B, is initiated from an upstream GUG codon

Abstract: The expression of the cyclin-dependent kinase inhibitor p15 INK4B in normal cells after induction with TGF-b1, or following overexpression from an adenovirus-encoded cDNA, appears on an SDS-polyacrylamide gel as a doublet. Here, the underlying mechanism behind the synthesis of the two species has been studied. By expressing cDNAs truncated at their 5' end, we found that the synthesis of the more slowly migrating form, called p15.5 INK4B , is dependent on a sequence upstream of the ®rst AUG codon thought to ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…The weakness explains why non-AUG codons are usually used only as supplementary initiation sites; i.e. ribosomes initiate at an upstream non-AUG codon in addition to initiating at the first AUG (Carroll and Derse, 1993;Chang and Wang, 2004;Fütterer et al, 1997;Fuxe et al, 2000;Portis et al, 1994). The non-AUG initiated protein serves a useful function in those examples; but in some other cases, the N-terminally extended form of the protein has no biological relevance (Miles et al, 2003).…”
Section: Context Effects On Recognition Of Aug (Or Other) Start Codonsmentioning
confidence: 98%
“…The weakness explains why non-AUG codons are usually used only as supplementary initiation sites; i.e. ribosomes initiate at an upstream non-AUG codon in addition to initiating at the first AUG (Carroll and Derse, 1993;Chang and Wang, 2004;Fütterer et al, 1997;Fuxe et al, 2000;Portis et al, 1994). The non-AUG initiated protein serves a useful function in those examples; but in some other cases, the N-terminally extended form of the protein has no biological relevance (Miles et al, 2003).…”
Section: Context Effects On Recognition Of Aug (Or Other) Start Codonsmentioning
confidence: 98%
“…On SDS-polyacrylamide gels, we consistently observed that p15 INK4B migrated as a doublet. These two species, called p15.5 INK4B and p15 INK4B , were analyzed to determine the molecular and possible functional differences, also reported by Fuxe et al [20]. They concluded that there were no functional differences in the capacity of the two forms.…”
Section: Methodsmentioning
confidence: 99%
“…This may be explained by the fact that our initial mutation of the primary AUG to GUG did not affect levels of luciferase activity, indicating that this mutation does not completely abolish the potency of the translation start codon. In fact GUG has been shown in other systems to function as an alternative start codon (19). Further mutation of the start site and the flanking nucleotides attenuated ribosome binding, but it did not completely abolish it.…”
Section: Discussionmentioning
confidence: 99%